(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Ortho-hydroxyformylchromones are convenient synthones for the construction of linear and angular hetarenochromones. Usually, 7-hydroxy-6-formylchromones were synthesized by oxidation of natural linear furochromones: visnagin and kellin and their synthetic analogues. The Duff reaction, which is the formylation of phenols in the ortho-position by heating with hexamethylenetetramine followed by acidic hydrolysis of intermediate imine, was also used to convert 7-hydroxychromones into 7-hydroxy-6-formylchromones, but in this case there were some difficulties because of the passivity of position 6 in 7-hydroxychromones compared to position 8 to the electrophilic attack. Thus, for the preparation of 7-hydroxy-6-formylchromones, it is necessary to use 8-substituted derivatives and to provide formylation for a long time. A method for the synthesis of 7-hydroxy-6-formylchromones based on 8-substituted 7-hydroxy-6-dialkylaminomethylchromones and hexamethylenetetramine was developed using the Duff reaction conditions. This method was demonstrated on the synthesis of 7-hydroxy-2,8-dimethyl-4-oxo-3-phenoxy-4H-6-chromenecarbaldehyde from 6-dimethylaminomethyl-7-hydroxy-2,8-dimethyl-3-phenoxy-4H-4-chromenone and hexamethylenetetramine in glacial acetic acid at reflux. It should be noted that when carrying out this reaction under heating on a water bath with subsequent hydrochloric acid hydrolysis only Mannich base hydrochloride was isolated from the reaction mixture. The starting 6-dimethylaminomethyl-7-hydroxy-2,8-dimethyl-3-phenoxy-4H-4-chromenone was synthesized from 1-(2,4-dihydroxy-3-methylphenyl)-2-phenoxyethanone in three steps. Acylation of the latter with acetic anhydride in the presence of trimethylamine followed by condensation afforded 2,8-dimethyl-4-оxо-3-phenoxy-4Н-7-chromenylаcetate. Subsequent removal of acetyl protection resulted in 7-hydroxy-2,8-dimethyl-3-phenoxy-4H-4-chromenone, which on introduction into the Mannich reaction with bisdimethylaminomethane in dioxane gave rise to the desired 6-dimethylaminomethyl derivative.